1999
DOI: 10.1046/j.1537-2995.1999.39080834.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe delayed hemolytic transfusion reaction secondary to anti‐Ata

Abstract: Although anti-At(a) was previously described as being of uncertain clinical significance, this patient demonstrated the ability of the antibody to cause a severe delayed hemolytic transfusion reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The first paper referring to the At a blood group antigen, which can be responsible for severe hemolytic transfusion reactions 1 and mild hemolytic disease of the newborn, 2 dates back to the 1960s. Applewhaite et al 3 identified an antibody with a novel specificity in the serum of Mrs Augustine, when the red cells of her third child gave a positive direct antiglobulin reaction at birth.…”
Section: Introductionmentioning
confidence: 99%
“…The first paper referring to the At a blood group antigen, which can be responsible for severe hemolytic transfusion reactions 1 and mild hemolytic disease of the newborn, 2 dates back to the 1960s. Applewhaite et al 3 identified an antibody with a novel specificity in the serum of Mrs Augustine, when the red cells of her third child gave a positive direct antiglobulin reaction at birth.…”
Section: Introductionmentioning
confidence: 99%
“…A severe delayed HTR was also observed after multiple transfusions of At(a+) RBCs. 13 Recently, another case was reported in which a woman experienced an acute HTR attributed to anti-At a . 15 In addition, anti-At a has also been shown to be involved in rapid destruction of 51 Cr-labeled At(a+) RBCs in vivo and to give positive results in in vitro functional assays.…”
Section: Discussionmentioning
confidence: 99%
“…Only one example of a case of mild HDFN caused by anti‐At a has been reported previously . Also, as an example of a severe haemolytic transfusion reaction caused by anti‐At a has been reported it is important to ensure that compatible blood is available should the mother require transfusion postdelivery. Pregnancies where there is a risk of HDFN in which the mother is At(a−) require careful monitoring and management to minimize any requirement for transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The negative phenotype At(a−) is rare worldwide and has only been identified in individuals of West African or West Indies ancestry . Examples of anti‐At a antibodies have been described in At(a−) individuals although the clinical significance has remained largely uncharacterized due to the rarity of reagents to detect this phenotype.…”
Section: Introductionmentioning
confidence: 99%